Distributed Quantum Simulation on the VPE-qGM Environment - Maron, Adriano K.; Pinheiro, Anderson B.; Reiser, Renata H. S.; Pilla, Mauricio L. (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD), 2010)
This work describes a proposal for a platform focused on modeling and simulation (sequential or distributed) of quantum algorithms. More specifically, the integration between the environments VPE-qGM and VirD-GM is considered, providing a solution to the high computational cost associated to the simulation of quantum algorithms on classical computers. In this context, the algorithms are visually programmed and the details of distribution, communication and synchronization, required for the execution in distributed systems, are transparently managed by the execution environment. The validation and performance analysis consist in simulating a quantum search algorithm, obtaining results which demonstrate the performance gain of the platform compared to the sequential simulation.